LEGALISASI HUKUM WARIS DI INDONESIA : SUATU PENDEKATAN HISTORIS - Abdur Rahim (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2021)
A comprehensive understanding of how the history of the application of Islamic law, especially inheritance law in Indonesia so that it can occur and enter the national legal system, then examines the socio-economic history of Islamic law in Indonesia is the first step to answer it, especially in the historical aspects of Islamic law legislation. This historical study must also be traced from the earliest period, namely since the arrival of Islam to the archipelago, because the existence and position of Islamic law today cannot be separated from the history of Islam in the archipelago itself. With this historical approach, a complete picture will be seen of how the process of wrestling Islamic law legislation, especially inheritance, as well as the aspects and forms of legislation that occurs. This research was conducted through a descriptive analysis approach, therefore the contribution of concrete ideas about the history of the implementation of inheritance law in Indonesia by experts was found